HUBUNGAN PENDIDIKAN DAN STRATIFIKASI SOSIAL - Taufik Mukmin (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2018)
Education is expected to be able to play a role as a process of socialization in the community can run well. So that the socialization process can run smoothly and smoothly. Therefore, parents and family hope the school can carry out the socialization process well. In these institutions teachers in schools are seen as models and are considered able to carry out the mandate of parents (family and community) so that children understand and then adopt the cultural values of their community. The school has the duty to carry out efforts to divert the cultural values of the community by teaching values that are the way of life for the people and nation. To fulfill its functions and duties, the school establishes educational programs and curricula, along with pedagogical methods and techniques, so that the transmission process of these values runs smoothly and smoothly.